2015
DOI: 10.1007/s00464-015-4417-1
|View full text |Cite
|
Sign up to set email alerts
|

The uncinate process first approach: a novel technique for laparoscopic right hemicolectomy with complete mesocolic excision

Abstract: Laparoscopic right hemicolectomy with CME using the UFA provides adequate radicality according to the CME principles and seems feasible and as safe as an open technique. However, future trails will have to demonstrate whether the theoretical advantages of the UFA, with a higher degree of mobility and accessibility of the mesenteric root, translate into a significant clinical benefit, especially relative to the other laparoscopic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 18 publications
0
17
1
Order By: Relevance
“…While the medial-to-lateral access is performed in laparoscopic surgery, the mesenteric vessels are initially explored and divided and the medial mesenteric base of the colon is dissected, and finally the colonic lateral peritoneal attachments are separated [14][15][16]. BThe uncinate process first approach (UFA)^is a newly reported laparoscopic right hemicolectomy approach [9]. The key step of the UFA is the commencement of the dissection at the fourth part of the duodenum using a medial to lateral approach, thus mobilizing the whole mesenteric root posteriorly before the central parts of the mesenteric vessels are accessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the medial-to-lateral access is performed in laparoscopic surgery, the mesenteric vessels are initially explored and divided and the medial mesenteric base of the colon is dissected, and finally the colonic lateral peritoneal attachments are separated [14][15][16]. BThe uncinate process first approach (UFA)^is a newly reported laparoscopic right hemicolectomy approach [9]. The key step of the UFA is the commencement of the dissection at the fourth part of the duodenum using a medial to lateral approach, thus mobilizing the whole mesenteric root posteriorly before the central parts of the mesenteric vessels are accessed.…”
Section: Discussionmentioning
confidence: 99%
“…The primary step of the laparoscopic medial method is the ligation of the principal vessels at their origin within the mesenteric root. Benz reported Bthe uncinate process first approach (UFA)^recently [9], and the beginning of the dissection at the duodeno-jejunal flexure is the key step of the UFA.…”
mentioning
confidence: 99%
“…lon cancer have improved over the last decade [5,6] . Increasing evidence has reported that CMEs contribute to a decreased recurrence rate and increased five-year survival [4,7,8] .…”
mentioning
confidence: 99%
“…As previously published by our group the operation was performed using the 'uncinate process first' approach [3,4]. The main difference compared to the operation in an adult patient was the very large lymph nodes around the mesenteric root and the base of the transverse mesocolon which are seen physiologically in children.…”
Section: Supporting Informationmentioning
confidence: 99%